Direct medical cost of children and adolescents epilepsy at a university setting in Croatia - Prpić, Igor, liječnik (Array, 2009)
Abstract: The aim was to study the direct medical cost of epilepsy in children and adolescents and to determine the impact of epilepsy type and child’s age on total costs of treatment. One-year prospective, prevalence based, »bottom up« analyses of sixty-nine (69) children with epilepsy (International League Against Epilepsy criteria was used). Direct medical costs were calculated by summing annual costs of hospital care, outpatient visits and antiepileptic drug (AED) treatment. The average annual cost per patient was 1293.0 €. The costs of hospital admissions were 942.9 € (72%), followed by drug treatment 240.0 € (19%) and outpatient medical services 121.2 € (9%). The costs of epilepsy were significantly higher for children under 5 year of age. AED costs were statistically significantly lower for children who received traditional AED (€122.0) than modern AED (571.2€). The costs of epilepsy in children and adolescents in Croatia are congruent to those of developed countries. Costs significantly varied regarding the child’s age. The cost of illness studies are an important first step towards the rational use of available resources